1994
DOI: 10.1136/hrt.72.5.408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bystander initiated cardiopulmonary resuscitation on ventricular fibrillation and survival after witnessed cardiac arrest outside hospital.

Abstract: Objective-To describe the proportion of patients who were discharged from hospital after witnessed cardiac arrest outside hospital in relation to whether a bystander initiated cardiopulmonary resuscitation. Patients-Al1 patients with witnessed cardiac arrest outside hospital before arrival of the ambulance and in whom cardiopulmonary resuscitation was attempted by the emergency medical service in Gothenburg during 1980-92. Results-Cardiopulmonary resuscitation was initiated by a bystander in 18% (303) of 1660 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(48 citation statements)
references
References 11 publications
4
43
0
1
Order By: Relevance
“…This could be looked upon as a disappointing finding. The increase in bystander cardiopulmonary resuscitation [6][7][8] as well as a shortened interval from collapse to defibrillation should both increase the proportion of patients found in ventricular fibrillation. However, the increasing age of the victims might indicate a higher proportion of patients with severe underlying disease which could lower the possibility of finding them in ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 97%
“…This could be looked upon as a disappointing finding. The increase in bystander cardiopulmonary resuscitation [6][7][8] as well as a shortened interval from collapse to defibrillation should both increase the proportion of patients found in ventricular fibrillation. However, the increasing age of the victims might indicate a higher proportion of patients with severe underlying disease which could lower the possibility of finding them in ventricular fibrillation.…”
Section: Discussionmentioning
confidence: 97%
“…In 1994, Herlitz et al demonstrated a three-fold increase in survival of VF patients who received bystander CPR as compared with the study group who did not receive bystander CPR. 7 The King County, Washington, group led by Rea compared survival rates for adult cardiac arrest victims who received no bystander CPR, those who received bystander CPR before EMS arrival requiring dispatcher instruction, and those who received bystander CPR without dispatcher assistance. In addition to finding a 25% increase in the rate of bystander CPR when dispatcher-assisted CPR was utilized, the researchers noted that dispatcher-assisted bystander CPR increased survival.…”
Section: Discussionmentioning
confidence: 99%
“…After prolonged untreated cardiac arrest, severe and progressive energy imbalances develop (26 -28). Chest compressions produce approximately 46% of the prearrest stroke volume values (29), restore minimal myocardial and cerebral blood flows, and thereby prime the heart for successful defibrillation and minimize ischemic brain damage (30).…”
Section: Discussionmentioning
confidence: 99%